Count Agenor Gołuchowski’s Plan to Occupy the Straits (1895) - Serdar Bay (Journal of Universal History Studies, 2025)
When Count Agenor Gołuchowski became Austro-Hungarian Foreign Minister in May 1895, he adopted a cautious foreign policy aimed at preserving the status quo in the Near East and preventing Russian expansion towards the Straits and the Balkans. However, the Armenian events in Istanbul created considerable public pressure on the European Powers and revived fears about the Eastern Question. Faced with the risk of Russian intervention and growing instability, Gołuchowski sought to reaffirm the importance the Concert of Europe by proposing a naval demonstration and a plan for the occupation of the Straits in November, 1895. Although he expected strong support from Britain, his ally in the Mediterranean Treaty, the British Cabinet ultimately opposed the plan. The British Admiralty, led by Goschen and Richards, raised serious objections to the plan, arguing that Sultan Abdülhamid II’s recent fortification of the Dardanelles made sea passage impossible without significant land support. Moreover, Russia’s firm opposition to any military intervention further isolated Gołuchowski’s proposal and ultimately forced its withdrawal. As a result, the plan collapsed, revealing the fragility of European collective action on the Eastern Question. Drawing mainly on British and Ottoman archival documents, this study argues that the failure of Gołuchowski’s initiative not only exposed the limits of European collective diplomacy, but also accelerated the decline of Austro-Hungarian influence in the Balkans. It also highlights how the collapse of the plan signalled a wider weakening of the Council of Europe in the management of the Ottoman crisis, drawing attention to the growing divergence among the Great Powers over the Eastern Question. By analysing diplomatic correspondence, naval assessments and parliamentary debates of the period, the study provides a comprehensive understanding of how strategic miscalculations, divisions within the British Cabinet and assertive Russian diplomacy frustrated Gołuchowski’s ambitions and reshaped regional alignments. This case study reveals the limits of naval diplomacy and the fragility of European unity in managing the Eastern Question at a critical juncture.